If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -62 = 25 Reorder the terms: -62 + x = 25 Solving -62 + x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '62' to each side of the equation. -62 + 62 + x = 25 + 62 Combine like terms: -62 + 62 = 0 0 + x = 25 + 62 x = 25 + 62 Combine like terms: 25 + 62 = 87 x = 87 Simplifying x = 87
| 8x+12=4x+32 | | 21n+7=7n | | 76.50-31.41=t | | 650+825+c=2200 | | [3-5]+13= | | -5(d-8)=6 | | 2n+7n=18 | | -5x-y=-10 | | 120+2x=180 | | 2a-3=9a-19 | | 7=-2j+4 | | 8z+-2=3z+6 | | 3/4w-1/8=9/16 | | 3y^2-3u^4y^2=0 | | log(9x+6)=1 | | 23423=x^2+35x+30 | | 5(5x+1)=3x-8x | | 8x^2-5x+k=0 | | 4(w-1)=4 | | -325+75=t | | -[(2x+1)-5(x-4)]+4=10(x+3) | | 5=-5v+8 | | 2.5n-(-10)= | | 2x^2-4x-132=0 | | 2y+5x=-6 | | 86+(38+x)(2)= | | 6x^2=-72x | | -13-4=n | | X-6=-5whatisx | | 8-7n=57 | | x=-432 | | 6x-2yi=6+8i |